Characterization of a spark ignition motor, operated with biogas for electricity generation - García Armas, Juvenal Viviano (2020)
The objective of the study was to characterize the behavior of a spark ignition engine as an energy source, for the purpose of electricity generation, using as fuel, biogas, generated from animal excreta in a tubular biodigester, said biodegradation under anaerobic conditions resulted in a biogas composed of 59.5% methane; 39.3% carbon dioxide; 0.2% oxygen and 1% other gases, at the outlet in the conduction pipe, filters made of steel were placed to eliminate the hydrogen sulfide. This biogas fed a 7hP Otto motor coupled to a 3kW single-phase alternator, with a power factor of 0.7, coupled to a 2kW resistor bank, the input variables were the RPM, and the resistances, the results referred to the behavior engine for power, torque, hourly and specific consumption. They were similar in both gasoline and biogas. Differing in the magnitude developed, being less than the biogas by an average 25%. Maximum values were 1500W gasoline and 1250W biogas. In the carbon monoxide emissions with biogas, it did not exceed 40 ppm., While with gasoline it exceeded 450ppm. Biogas is a feasible and production alternative to be used as fuel in Otto engines, for electrical or mechanical generation purposes; they also mitigate environmental pollution and the greenhouse effect.